Romania : Poverty Assessment, Volume 1. Main Report - World Bank (Washington, DC, 2013)
This poverty assessment for Romania covers the period from 1995 to 2002, since the last World Bank poverty analysis reviewed the evolution of poverty from 1989 to 1994, the early years of transition from a socialist to a market economy. This assessment's objective is to understand how poverty has evolved and how economic growth and social protection programs, 10 percent of GDP, have affected poverty, as Romania prepares for accession to the European Union. The paper focuses on monetary dimensions of well-being, or consumption, to inform the policy dialogue in Romania on the extent and dynamics of poverty. The results are based on two comparable, nationally representative surveys: (i) the Romanian Household Budget Survey (ABF, upon its Romanian acronym) for the period 2001- 2002; and (ii) the Integrated Household Survey (AIG) for the period 1995-2000. Other dimensions of deprivations have been captured for 2002 using the Living Conditions Survey (ACOVI). While concentrating on monetary poverty, the paper captures dimensions of material poverty such as caloric intake; crowding and living conditions, and ownership of essential durables. In addition, it assesses poverty defined as capability to function in society, or adequate level of investments in health or education, or the lack of unemployment. Finally, the report reviews community poverty and perceptions of poverty. First, the changing economic structure is briefly described, as is the evolution of macroeconomic management. Second, the assessment is fitted into the context of the broader Bank program of analysis and lending. The rest of the paper is arranged as follows: a poverty profile (Chapter 2), an analysis of the impact of growth on poverty (Chapter 3), of labor force participation, unemployment and poverty (Chapter 4) and of social protection and poverty (Chapter 5). Detailed background papers are provided in Volume 2.